2021
DOI: 10.3389/fcimb.2021.627917
|View full text |Cite
|
Sign up to set email alerts
|

Fingolimod Potentiates the Antifungal Activity of Amphotericin B

Abstract: Candida albicans (C. albicans) is an opportunistic human fungal pathogen that can cause severe infection in clinic. Its incidence and mortality rate has been increasing rapidly. Amphotericin B (AMB), the clinical golden standard antifungal agent, has severe side effects that limit its clinical application. Thus, lowering the concentration and increasing the efficacy of AMB in a combinatorial antifungal therapy have been pursued by both industry and academia. Here we identify that fingolimod (FTY720), an immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…In line with our study, a recent ex vivo study by Wei and colleagues pointed to the fungicidal effect of FTY720, which synergized the effect of amphotericin B [39]. Wei et al showed that this fungicidal effect is present against non-albicans Candida spp., Saccharomyces cerevisiae, and Cryptococcus neoformans as well as C. albicans [39]. They also showed that 0.011 mg/ mL of FTY720 affects C. albicans' growth rate similar to 0.08 mg/L of amphotericin B [39].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In line with our study, a recent ex vivo study by Wei and colleagues pointed to the fungicidal effect of FTY720, which synergized the effect of amphotericin B [39]. Wei et al showed that this fungicidal effect is present against non-albicans Candida spp., Saccharomyces cerevisiae, and Cryptococcus neoformans as well as C. albicans [39]. They also showed that 0.011 mg/ mL of FTY720 affects C. albicans' growth rate similar to 0.08 mg/L of amphotericin B [39].…”
Section: Discussionsupporting
confidence: 91%
“…Wei et al showed that this fungicidal effect is present against non-albicans Candida spp ., Saccharomyces cerevisiae , and Cryptococcus neoformans as well as C . albicans [ 39 ]. They also showed that 0.011 mg/mL of FTY720 affects C .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations